Decision to delivery interval in emergency cesarean section and its association with perinatal outcome - Khatoon, Fareha; Singh, Amrita; Shamsi, Sumaiya; Ahmad, Ayesha; Teotia, Nikunj (Asian Journal of Medical Sciences, 2021)
Background: Decision to delivery [DDI] interval is the time interval between decision for caesarean section [CS] and delivery of baby. The ideal DDI for emergency CS is not known; there is controversy over the best DDI to avoid preventable perinatal morbidity and mortality. Aims and Objectives: This study was conducted to find out the DDI we could achieve for Category-1 and Category-2 CS and evaluate our findings against the recommendations by National Institute for Clinical Excellence [NICE]. We also studied the association of DDI with perinatal outcome and explored the reasons for prolongation of DDI. Materials and Methods: This was a prospective study conducted over a period of 6 months. All women who underwent CS and meeting the inclusion criteria were recruited for the study. DDI was calculated as the time interval between decision making and delivery of baby, in minutes [min]. Data was collected for maternal socio-demographic variables, CS indication and complications and perinatal outcome. Analysis was done using SPSS version 21.0. Results: Ninety out of one hundred eighty-one CS was evaluated. Cases were grouped as Group I [including cases where we could achieve the recommended DDI] and Group II [including cases where we could not achieve the recommended DDI]. The average DDI was 55.04 min for category- 1 and 55.13 for category-2 CS. For Category-1 CS, all the cases qualified for entry into Group II because we could not achieve a DDI of 30 min. For Category-2 CS there were 22 cases in Group I and 14 cases in Group II. There was no difference in perinatal outcome between the groups. Conclusion: It was not feasible to achieve the 30 min DDI for Category-1 CS in the present study. The DDI of 30-75 min for Category-2 could be achieved in 61.11% cases. The most common reason for failure to achieve the recommended DDI was related to issues with anaesthesia in the pre-operative room as well as inside the theatre in the pre-induction phase. Delay in category-2 CS was not associated with poor perinatal outcome.